Creating a Religious Culture Program to Enhance the Islamic Values of Middle School Students in Private Education - Aisyah Purnama Sari Siregar; Ali Imran Sinaga; Nirwana Anas (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
The objective of this study is to assess the viability and effectiveness of religious culture programs in elucidating the religious inclinations of students in private schools. The study adopts a 4-D model: definition, design, development, and implementation. The study's population comprised all ninth-grade students, with one class (IX-1) as the control group and another class (IX-2) as the experimental group, totaling 30 participants. Student responses were analyzed in small groups of 10 students and a limited field group of 30. The research outcomes indicate: First, the religious culture program's feasibility was confirmed through validation by three experts. The program's feasibility was assessed based on three components: content, language, and design. The validation results from the three experts revealed the following average scores: 81.82 for the content component, 77.88 for the language component, and 69.79 for the presentation component. These scores fall within the excellent category, signifying that the religious and cultural programs can be employed with minor revisions. Second, the effectiveness of the religious culture program in enhancing students' religious attitudes was assessed by comparing the control class and the experimental class. The average score for the control class was 64.00, whereas the average score for the experimental class was 72.22. The data analysis results indicate that an effective religious culture program can positively impact the Islamic character development of ninth-grade students at Madani Middle School, particularly in Islamic religious education.